2014
DOI: 10.1134/s1063780x14090062
|View full text |Cite
|
Sign up to set email alerts
|

Study of the termination phase of plasma production and the formation of magnetic flux breakthroughs during wire array implosion

Abstract: The phenomenon of magnetic flux breakthrough into a wire array during its implosion was studied experimentally at the Angara 5 1 facility. It is shown that breakthroughs develop in the final stage of plasma production from the wire material and occur near the initial wire position. The spatial distributions of the azi muthal magnetic field within tungsten, molybdenum, copper, and aluminum wire arrays were studied using magnetic probes. The distributions of the azimuthal magnetic field B ϕ (z, t) along the arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The times of the end of plasma production on the outer T pl out and inner T pl in arrays were determined from measurements of the derivative of the total current dI/dt and voltage U (see curves 1 and 2 in figures 2(a)-4(a)) in the following way. Based on the experiments [37,52] with single wire arrays made of various substances, it was shown that at the stage of the end of plasma production, when ṁ → 0, in the region where the wires (or fibers) are located, the magnetic flux breaks into the interior of the array. This leads to an increase in the inductance of the wire array and a violation of the proportionality between the voltage U and the derivative of the total current dI/dt.…”
Section: Final Stage Of Z-pinch Plasma Compression Trailing Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…The times of the end of plasma production on the outer T pl out and inner T pl in arrays were determined from measurements of the derivative of the total current dI/dt and voltage U (see curves 1 and 2 in figures 2(a)-4(a)) in the following way. Based on the experiments [37,52] with single wire arrays made of various substances, it was shown that at the stage of the end of plasma production, when ṁ → 0, in the region where the wires (or fibers) are located, the magnetic flux breaks into the interior of the array. This leads to an increase in the inductance of the wire array and a violation of the proportionality between the voltage U and the derivative of the total current dI/dt.…”
Section: Final Stage Of Z-pinch Plasma Compression Trailing Plasmamentioning
confidence: 99%
“…However, the final stage of compression of wire arrays [36][37][38] and thin metal shells [39] is accompanied by the development of various instabilities. One of the main and dangerous types of instabilities of the outer boundary of the plasma, accelerated by the pressure of the magnetic field of its own current, is the magnetic Rayleigh-Taylor (MRT) instability.…”
Section: Introductionmentioning
confidence: 99%